Familial and Contextual Influences on Children’s Prosocial Behavior: South African Caregivers as Adult Protective Shields in Enhancing Child Mental Health - Parchment, Tyrone M. (Glob Soc Welf, 2016)
BACKGROUND: The mental health of children is too frequently overlooked in resource scarce low and middle-income countries. South Africa represents one of many country contexts struggling to meet the mental health needs of large numbers of young people. Family caregivers have been identified as potential protective influences on child mental health, even for those children being reared with high exposure to poverty. METHODS: This paper explores contextual influences on South African caregiver’s social-emotional health living in communities impacted by poverty and food insecurity as they attempt to support their children’s prosocial skills and behavior. Structural Equation Modeling (SEM) was employed to explore the relationship between neighborhood social cohesion and caregiver report of child’s prosocial behavior as mediated by the caregiver’s mental health (n=478). RESULTS: Results indicated that the more caregivers experience their communities as socially cohesive, the better their social-emotional well-being, thus positively related to their reports of children’s prosocial behavior. Furthermore, when there is a male head of household, caregivers reported better social-emotional well-being in comparison to female headed of household. The more food secure caregivers also were likely to report better general health. CONCLUSION: South African community characteristics and caregivers, in particular male caregivers, are integral to child and caregiver mental health. Future research should examine the impact of interventions that mobilize community and caregiver supports for children’s prosocial behavior and mental health.